Characterization of blood mononuclear phagocytes in Phrynops hilarii (Chelonia Chelidae) - Pitol, Dimitrius Leonardo [UNESP] (2007)
The localization of peroxidase activity in different cell regions is used as a criterion for the classification of the stage of maturation of mammalian mononuclear phagocytes with a positive peroxidase reaction indicating the presence of monoblasts, promonocytes, monocytes and macrophages. In this study it was evaluated the peroxidase activity of blood mononuclear phagocytes of this turtle detected at different stages of differentiation. The present observations suggest that, in turtles, the differentiation of mononuclear phagocytes occur in the blood circulation, in contrast to animals, where only are monocytes in circulating blood and macrophage differentiation occurs in other body compartments. © 2007 Sociedad Chilena de Anatomía.